2020
DOI: 10.1002/pmic.202000012
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Myofibrillar Proteome as a Way to Better Understand Differences in Bovine Meats Having Different Ultimate pH Values

Abstract: Influence of ultimate pH (pHu) on the occurrence of defective meats known as dark, firm, and dry (DFD) meats has been studied through a proteomic approach at early post‐mortem times. The myofibrillar sub‐proteome of longissimus thoracis et lumborum muscle from twelve loin samples from Asturiana de los Valles x Friesian yearling bulls, previously classified into two groups of six samples according to their pH values (normal, pHu < 6.0 and high, pHu ≥ 6.0), is analyzed at 24 h post‐mortem. Fractionation/enrichme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…A recent LC–MS/MS‐based proteomics study showed that proteins involved in glycogenolysis and mitochondrial electron transport may facilitate DC through increased oxygen consumption (Kiyimba et al., 2021). Unlike previous studies (Franco et al., 2015; Fuente‐Garcia et al., 2020), myosin light chain 1‐isoforms were not differentially abundant between high pH and normal beef. Another study revealed that glutaryl‐CoA dehydrogenase abundance has a strong correlation with DC and meat color, warranting further investigation (S. Wu et al., 2020).…”
Section: Potential Markerscontrasting
confidence: 90%
See 1 more Smart Citation
“…A recent LC–MS/MS‐based proteomics study showed that proteins involved in glycogenolysis and mitochondrial electron transport may facilitate DC through increased oxygen consumption (Kiyimba et al., 2021). Unlike previous studies (Franco et al., 2015; Fuente‐Garcia et al., 2020), myosin light chain 1‐isoforms were not differentially abundant between high pH and normal beef. Another study revealed that glutaryl‐CoA dehydrogenase abundance has a strong correlation with DC and meat color, warranting further investigation (S. Wu et al., 2020).…”
Section: Potential Markerscontrasting
confidence: 90%
“…Although this study identified protein biomarkers related to meat quality, the SDS–PAGE‐based electrophoretic separation approach may have obscured the identification of some differentially abundant proteins due to the potential co‐migration of various proteins in a single band. In another study, desmin, pyruvate kinase isoform X1, myosin light chain 1/3, and myosin 1 and 2 isoforms were identified as high pH bovine meat and preslaughter stress indicators (Fuente‐Garcia et al., 2020). A recent LC–MS/MS‐based proteomics study showed that proteins involved in glycogenolysis and mitochondrial electron transport may facilitate DC through increased oxygen consumption (Kiyimba et al., 2021).…”
Section: Potential Markersmentioning
confidence: 99%
“…Previous studies have shown that animals mixed during transport and lairage are more affected by pre-slaughter stress and they have also been related to higher post-mortem glycolytic metabolism [ 9 , 58 ]. Moreover, lower abundance of PKM was previously found in myofibrillar subproteome of high pH24 meat [ 26 ]. Thus, the lower levels of PKM found in the myofibrillar fraction of mixed animals in the present study can be explained by the glycogen depletion occurring due to PSS caused by the mixing procedure before slaughter.…”
Section: Resultsmentioning
confidence: 96%
“…The post-mortem concentration of these proteins has been previously associated with pork and beef tenderness [ 50 , 51 ], and belong to the robust list of biomarkers of beef tenderness shortlisted by Gagaoua et al [ 21 ]. Increased proteolysis of MYL1 has also been described in dark-cutting beef [ 22 , 26 ]. It is worthy to note that myosin lights chains were also identified as biomarkers of several beef color traits [ 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation